PENDUGAAN EROSI DAN NERACA AIR EMBUNG DI WILAYAH PERBATASAN KABUPATEN BELU NUSA TENGGARA TIMUR - Widiyono, Wahyu (Jurnal Rekayasa Lingkungan)
Embung as a man made water reservoir is one of methods to overcome the water shortage in the border area, Belu District, East Nusa Tenggara Province. A number of 27 embungs were built by Regional Government in this area. Embung water and environment management is the main problem to sustain water resource. The research to inventory and identify of vegetation, to predict erosion, to monitor water balance, and to optimize water utilization were conducted, in 2005-2008. The research was undertaken in Embung Leosama. Methods were survey, observation, monitoring and analysis. Results were: (1). There were 7 species and 90 individual number of tree; (2). Prediction of erosion was 97.383 ton/ha/year; (3). Water depth as indicator of embung water balance was decrease due to a little rainfall volume in rainy season 2006/2007; but it was increase in 2007/2008; (4). Embung water can be optimized for drinking cattle, horticulture, nursery and regreening irrigation.Key Words: embung, erosion, water balance.